High-intensity intermittent exercise induces a potential anti-inflammatory response in healthy women across the menstrual cycle - Minuzzi, Luciele Guerra [UNESP]; Lira, Fábio Santos [UNESP]; de Poli, Rodrigo Araújo Bonetti [UNESP]; Fialho Lopes, Vithor Hugo [UNESP]; Zagatto, Alessandro Moura [UNESP]; Suzuki, Katsuhiko; Antunes, Barbara M. [UNESP] (Elsevier, 2022)
Aim: This observational study aimed to examine cytokine responses to high-intensity intermittent exercise (HIIE) in the follicular and luteal phases of the menstrual cycle. Methods: Fourteen healthy women (24 ± 2 years; body mass index [BMI]: 22.8 ± 1.9 kg⋅m2; maximal oxygen consumption [V̇O2max]: 41.5 ± 4.1 mL⋅kg−1⋅min−1) with regular menstrual cycles were randomly assigned to 4 experimental sessions, 2 during the follicular and 2 during the luteal phase. V̇O2max and maximum aerobic velocity (MAV) were determined prior to the experimental sessions through a graded exercise test during both follicular and luteal phases. Seventy-two hours after having completed the graded exercise test, all participants performed a HIIE session (10 x 1-min sprints with 1 min of rest) at 90% of their MAV. Serum concentrations of TNF-α, IL-6, IL-10 and IL-17 were measured before (Pre), immediately after (Post) and 1 h after (1 h Post) the HIIE sessions. Results: Pre-exercise concentrations of TNF-α and IL-10 were significantly higher in the luteal phase compared to the follicular phase (P < 0.01), with no differences seen on IL-6 and IL-17, demonstrating an altered inflammatory status in the luteal phase. There was a significant interaction for IL-10 concentration (P < 0.01) with reductions in both luteal (Pre vs Post, 95 %CI: 1.086 to 6.156; and Pre vs 1 h Post, 95 %CI: 1.720 to 9.013, P < 0.01) and follicular phase (Pre vs 1 h Post, 95 %CI: 0.502 to 7.842, P < 0.05). Despite no significant phase × time interaction for TNF-α concentration, its concentration at 1 h Post was significantly lower compared to Pre in the luteal phase analysis (Pre vs 1 h Post, 95 %CI: 0.71 to 14.06; P < 0.05). These results are in agreement with IL-10 responses, highlighting a reduction on the inflammatory status after exercise. Conclusion: Mostly during the luteal phase, high-intensity intermittent exercise modulates cytokine responses, thus impacting exercise recovery. In this scenario, high-intensity intermittent exercise emerges as a non-pharmacology strategy to regulate inflammatory responses on healthy women who were affected by an inflammatory state given their menstrual cycle.
Keywords: Follicular phase; Inflammation; Luteal phase; Menstrual phase; Physical exercise; Woman